IMPLEMENTASI PERMAINAN TRADISIONAL PADA MATA KULIAH PENDIDIKAN JASMANI DAN OLAHRAGA MAHASISWA PGMI ANGKATAN 2016 UNIVERSITAS ISLAM MALANG - Megawati Megawati; Muhammad Afifulloh; Muhammad Sulistiono (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2020)
The purpose of this study was to determine the planning and application as well as the supporting factors and inhibitors of traditional games in physical education and sports courses for PGMI strata 1 class 2016 Islamic University of Malang students. Qualitative approach with descriptive type. Data collection techniques are interviews and documentation. The application of traditional games in physical education and sports courses was carried out by PGMI students in 2016. Some of the games played were sodor carts, jump rope, railing, bentengan, cats and rats. Supporting factors and obstacles to physical readiness, material and classroom management.